Carnivore space use shifts in response to seasonal resource availability - Nathan J. Svoboda; Jerrold L. Belant; Dean E. Beyer; Jared F. Duquette; Patrick E. Lederle (Ecosphere, 2019)
Abstract Estimating spatial and temporal resource use and partitioning among carnivore species varies based on life history and is critical to understanding ecological relationships of sympatric carnivores and their prey. Temporal variation in food availability can have a substantial influence on distribution, foraging behavior, prey selection, and population dynamics of carnivores. We investigated shifts in space use of black bears (Ursus americanus), bobcats (Lynx rufus), coyotes (Canis latrans), and gray wolves (C. lupus) in response to seasonal availability of white‐tailed deer (Odocoileus virginianus) fawns in Michigan, USA, May–August 2009–2011. We used generalized linear mixed models to identify whether probabilistic fawn space use resulted in shifts in carnivore space use from deer pre‐parturition (PPP, 1 May–24 May) to fawn limited mobility (LMP, 25 May–30 June) and social mobility (SMP, 1 July–31 August) periods. We developed a rule‐based algorithm to identify “clusters” of carnivore GPS locations and investigated carnivore clusters to identify fawn predation sites. Carnivores shifted space use among periods, but responses varied among species regarding fawn space use. Black bears selected against areas with greater fawn use during LMP and selected areas with greater fawn use during SMP. We suggest black bear space use was unrelated to fawn space use and reflected availability of vegetative forage. Bobcats selected areas with greater fawn use during LMP and SMP. Coyotes were indifferent to areas where fawns occurred during LMP but selected against areas with greater fawn use during SMP, likely foraging on alternative prey. Coyotes were spatially constrained by wolves, selecting against areas with greater wolf use during LMP and SMP. Wolves selected against areas with greater fawn use during LMP and SMP and selected areas near habitat edges and areas containing livestock carcasses. Carnivore responses to fawn white‐tailed deer distribution and vulnerability were congruent with life history strategies, resulting in space use shifts in response to temporarily abundant resources. Carnivores did not overall rely predominantly on fawns, likely shifting their space use to maximize intake of other seasonal resources. These events provide additional insight into life history strategies among co‐occurring species and dynamics of multi‐species predator–prey systems.